Altruistic Leadership and Employee Creativity with Intrinsic Motivation as Mediation - Jumarno; Rahmat, Adi; Heri, Helwen (SAINS ORGANISASI, 2023)
This research aims to investigate the impact of altruistic leadership on employee creativity. In depth, this research is to investigate and explain the influence of altruistic leadership on employee creativity through intrinsic motivation variables as mediation. The location of this research was the District Civil Service Police Unit. Rokan Hulu Province Riau. This study collected data by distributing questionnaires to employees using simple random sampling techniques. So the sample used in this research was 84 respondents. Research data analysis was processed using smartPLS version 3.0 software to analyze data and determine the relationship between constructs. The results of direct hypothesis testing. The path coefficient value of altruistic leadership on employee creativity is 0.674, which is positive, which means that altruistic leadership has a positive effect on employee creativity. The path coefficient value of altruistic leadership on intrinsic motivation is 0.952, which is positive, which means that altruistic leadership has a positive effect on intrinsic motivation. The coefficient value on the intrinsic motivation path towards employee creativity is 0.324, which is positive, which means that intrinsic motivation has a positive effect on employee creativity. The fourth hypothesis indirectly shows that Intrinsic Motivation has a positive and significant effect in mediating the relationship between Altruistic Leadership and employee creativity. In this calculation, the PV value level of significance is obtained at 0.003 < 0.05